Perkembangan Ilmu Pengetahuan di masa Dinasti Umayyah (41-132 H/661-750 M) - Nurhasan Nurhasan (Buletin Al-Turas, 2006)
The Omayyad Dynasty is not only well known by its military power but also its development of science, such as Al-Qur'an studies (ulum al-Qur'an), language, history, islamic law (fiqh), Hadis, literature. medical. and chemistry